Limbal Relaxing Incision during Phacoemulsification for the Correction of Astigmatism - Mohammad Muneer Quraishy, Mehvash Hussain (Pakistan Journal of Ophthalmology, 2015)
Purpose: To determine the difference in mean post-operative astigmatism of patients having limbal relaxing incisions with phacoemulsification as compared to phacoemulsification alone for the correction of pre-existing corneal astigmatism. Material and Methods: This study was conducted in the Civil Hospital Karachi Eye Unit II, from 1 st December 2009 - 1 st December 2010, for duration of 12 months. Patients enlisted for phacoemulsification cataract surgery with coexisting astigmatism were recruited and divided into two groups. Eyes that underwent cataract surgery with limbal relaxing incisions (cataract LRI group) and eyes that underwent cataract surgery only (control group). All patients underwent a comprehensive baseline ophthalmic examination that included uncorrected visual acuity (UCVA) and best corrected visual acuity (BCVA), manifest refraction, anterior segment slit – lamp examination, 90 D examination of fundus, keratometry and ultrasound biometry. Patients were evaluated at 1st day, 1st month and 3rd month postoperatively Post-operative examination included BCVA, anterior segment slit-lamp microscopy and keratometry. The data thus obtained was analyzed on SPSS 17. Results: A total of 50 eyes (29 right eyes and 21 left eyes) of 44 patients were included in the study. Mean patients age was 61 yrs ± 11.3 yrs (range: 30 to 80) in the LRI group and 57 yrs ± 11.8 yrs (range 30 to 80) in the control group. Data analysis demonstrated statistically significant reduction in the mean postoperative astigmatism in the LRI eyes from 1.78 ± 0.81 D@125° (range: 0.75 to 3.70 D) preoperatively to 0.73 ± 0.71 D @ 130° (range: 0.0 to 2.70) in the 3rd postoperative month as compared to control group from 1.28 ± 0.41 D @ 145° (range: 0.75 to 1.97 D) preoperatively to 1.17 ± 0.57 D @ 144° (range: 0.10 to 2.30) p-value 0.021. There were no intraoperative complications or postoperative subjective complaints (such as halo or glare) in our patients. Conclusion: Limbal relaxing incisions performed during phacoemulsification surgery appear to be safe and effective procedure to reduce pre-existing corneal astigmatism. Key Words: Limbal relaxing incision, Phacoemulsification, Astigmatism.